Effect of Beam Power on Intermetallic Compound Formation of Electron Beam-Welded Cu and Al6082-T6 Dissimilar Joints - Darina Kaisheva; Georgi Kotlarski; Maria Ormanova; Borislav Stoyanov; Vladimir Dunchev; Angel Anchev; Stefan Valkov (Eng)
In this work, electron beam welds between Cu and Al plates were formed using different power modes, namely 1800 W, 2400 W, and 3000 W. The structure, microhardness, and tensile strength of the raw materials and the weld seams were studied. The low power of the electron beam resulted in the improper penetration and insufficient depth of the weld seam. The low power resulted in high cooling rates, which hindered the nucleation of the copper and aluminum particles. A number of intermetallic compounds (IMCs) were formed, including the metastable Cu9Al4 one. An increase in the power of the electron beam reduced the cooling rate and increased the miscibility between the materials. This resulted in the formation of a mostly homogeneous structure comprising an αAl solid solution and dendritic eutectic CuAl2 intermetallic compounds. A preferred crystallographic orientation of the aluminum phase was detected regarding the sample prepared using a power of 3000 W, forming a specific texture towards the {111} family of crystallographic planes, which is the closest-packed structure. This plane characterizes the highest chemical activity and the highest plasticity. As a result, this sample exhibited the best chemical bonding between the IMCs and the aluminum matrix and the best microhardness and tensile test values.